The subjects and the forms of the German black jokes in the book “Da bleibt kein Auge trocken” by Willy Millowitsch (1980) - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2023)
This article shows which subject matter is to be found in the German black joke. The material analysis includes 30 jokes taken from the book “Da bleibt kein Auge trocken” by Willy Millowitsch (1980). Besides the subjects to be found (violence, suffering and death) the form of the jokes and the sentence types appearing in the black jokes mentioned by Millowitsch are also important.